PEMBUATAN SERTA PEMELIHARAAN WASTAFEL FORTABLE UNTUK MEMUTUS PENYEBARAN COVID 19 DI BANJAR ADAT DENKAYU DELODAN WERDI BHUWANA - Janardana, I.G.N.; Wijaya, I.W.A.; Suartika, I.M.; Rinas, I.W. (Buletin Udayana Mengabdi; Vol 23 No 3 (2024): Buletin Udayana MengabdiDO - 10.24843/BUM.2024.v23.i03.p09, 2023)
Corona virus infection is a disease caused by the corona virus. To prevent the spread of COVID-19, regular hand washing with soap and water, or an alcohol-based hand sanitizer is highly recommended. Always keep a safe distance. At the end of 2020, the Banjar Adat Denkayu Delodan was hit by an epidemic and resulted in the death of residents and disruption of economic activities, social activities and religious activities. This problem is due to the lack of discipline in the community about wearing masks, washing hands and keeping a distance during activities as well as the unavailability of facilities such as hygienic portable sinks, and not spraying disinfectants regularly in the community. Based on this problem, it is very necessary to do community service by providing disinfectant spray equipment and portable sinks to break the spread of Covid-19, as well as make it easier to bring it to the location of social, customary and religious activities and can break the spread of Covid-19 in the community. The method used in this community service activity is to conduct counseling and provide prevention tools to the community. The results that have been achieved from community service in Banjar Denkayu Delodan are that the Disinfectant Spray Tool and Portable Sink have been used properly by the people of Banjar Denkayu Delodan, Werdi Bhuwana Village for the needs of social, customary and religious activities in Banjar Denkayu Delodan, Werdi Bhuwana Village. And has an impact on the occurrence of stopping the spread of Covid-19. Keywords: Covid-19, Spread, Termination, Prevention